2017
DOI: 10.3390/ijerph14080841
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Respiratory Diseases in the Regions of Northern Russia: Epidemiological Distinctions in the Results of a National Population Study

Abstract: The aim of the study is to investigate the epidemiological situation regarding chronic respiratory diseases in populations that inhabit different climatic–geographical regions of Russia, and to develop targeted programs for prevention of these diseases. Methods: (1) a comparative analysis of the standardized mortality data in Russia and other selected regions of the Russian North using the European standard for respiratory diseases, in a population aged 25–64; and (2) data from a randomized cross-sectional epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
(12 reference statements)
1
8
0
Order By: Relevance
“…The epidemiology and disease burdens of CRDs vary substantially worldwide. Previous studies have estimated the prevalence of CRDs at the regional or national level but not at the global level [3][4][5]. Understanding the prevalence and incidence trends of CRDs is vital for improving the control and prevention of CRDs.…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiology and disease burdens of CRDs vary substantially worldwide. Previous studies have estimated the prevalence of CRDs at the regional or national level but not at the global level [3][4][5]. Understanding the prevalence and incidence trends of CRDs is vital for improving the control and prevention of CRDs.…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that both the underlying population, region and local risk factors, the way the diagnosis was made, and underdiagnosis of COPD may play a role in explaining these differences. Artukhov et al [ 19 ] and Chuchalin et al [ 20 ] used stratified random cluster sampling; Gambaryan et al [ 21 ] selected subjects from the clinics. Notably, in many Central Asian countries, due to cultural and socioeconomic circumstances, patients go to the hospital only when the condition worsens, and not when the first symptoms appear, which also affects the underdiagnosis of RDs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Landis et al [ 22 ] recruited 301 participants of 40 years and older in Russia, and estimated the prevalence of COPD, based on a broad definition of self-reported physician diagnosis of COPD or chronic bronchitis or symptoms matching chronic bronchitis, at 9.2%. Artukhov et al [ 19 ], Gambaryan et al [ 21 ], and Chuchalin et al [ 20 ] found that the prevalence of COPD in Russia was 2%, 15.7%, and 15.3%. Age groups were ≥18 years old, 35–64 years old, and ≥18 years old, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations